Quantitative Determination of Fluoroquinolones in Contaminated Soils by HPLC with Solid-Phase Extraction - bashar hussin qassim (مجلة بغداد للعلوم, 2020)
This work reports the development of an analytical method for the simultaneous analysis of three fluoroquinolones; ciprofloxacin (CIP), norfloxacin (NOR) and ofloxacin (OFL) in soil matrix. The proposed method was performed by using microwave-assisted extraction (MAE), solid-phase extraction (SPE) for samples purification, and finally the pre-concentrated samples were analyzed by HPLC detector. In this study, various organic solvents were tested to extract the test compounds, and the extraction performance was evaluated by testing various parameters including extraction solvent, solvent volume, extraction time, temperature and number of the extraction cycles. The current method showed a good linearity over the concentration ranging from 1 – 300ng g-1 with correlation coefficients (r2 > 0.998) for all test compounds. Good recoveries were also obtained for the test compounds ranged from 89 – 99 %. The relative standard deviation (RSD) from intra-day and inter-day precision was lower than 7%, and the detection (LOD) and quantification (LOQ) limits ranged from 0.9 – 2.7ng g-1.Finally, the proposed method was applied to determine the target compounds in real soil samples irrigated with wastewater. The results confirm the presence of the test compounds in soils with values ranging from 1.9 – 4.6ng g-1, as well as the suitability of the proposed method to determine the test compounds in real soil matrix as well as the ability of the test compounds to accumulate in soils irrigated with sewage.